The Mental Health of New Thai Male Y-Genre Actors Who Has Less Than 3 Years Experience - Yospaiboon, Nalinee; Kanchanatawan, Buranee; Cheasuwantavee, Tavee (Journal of Dhamma for Life, 2025)
This study aimed to investigate the mental heath of the new Thai male “Y” genre actors who has less than 3 years acting experience. This qualitative research was conducted in 7 Thai male Y-genre actors based on literature reviews using semi-structured in-depth interviews, data analysis was performed through content analysis. The results shown positively, 100% seeing it as self worth, gaining more followers on social media or fame is the new generations needed. Only 14% is afraid of negative evaluation from society. In terms of mental health, challenges were evident: 71% faced family disputes in gender identity issue, while 61% encountered family objections to their career choice. 29% plan to continue working in entertainment industry while 71% began planning alternative career paths. This research underscores that the family dispute, fear of criticism, stress management, role transition becoming superstar and adaptive behavior significantly impact their mental health, self-perception, and overall well-being in both positive and negative impacts on their mental.